O embate entre o realismo científico e o empirismo construtivo de van Fraassen em Images of Science: as críticas pós The Scientific Image - Camargo, Josiel dos Santos (2021)
This paper aims to present the clash between van Fraassen's constructive empiricism and scientific realism in the work Images of Science, a compilation intended to present the realist criticism in response to the author's book The Scientific Image, where the latter had presented an innovative view in defense of an empiricist conception in philosophy of science. Given that scientific realism was on the rise in the mid-seventies, representing the main prevailing conception in philosophy of science since the weakening of logical empiricism, with the emergence of constructive empiricism, through the publication of The Scientific Image (1980), the empiricist mood was renewed. With the same intensity, realist reactions took over the debates, triggering a series of writings in this sense, one of them being Images of Science, which gathered a range of writings in defense of scientific realism in opposition to van Fraassen's central theses in the book in question. As a central objective, it is intended to evaluate, henceforth, the main issues involved in the clash, in order to better understand the new debate between realism and empiricism that was established from van Fraassen's positions and, likewise, point out the developments that followed from it, involving both conceptions. For this, the path to be outlined will consist, consequently, in understanding which are the central disputes from which both conceptions do not give up in defense of their positions. With this, the intention is to understand the reasons that led many of the scientific realists to feel provoked by van Fraassen's empiricism in his 1980 work. Since most of the new scientific realists adopted distinct positions in relation to their own central theses, it can be seen, beforehand, that something changed after van Fraassen's criticism and this change seems to represent an abandonment of part of this conception, especially the one linked to the metaphysical assumptions imbricated in this position. Beyond the debate in Images of Science, it is noted that van Fraassen also sought to strengthen his constructive empiricism in response to criticism, especially those related to some controversial points in his conception, such as the defense of a distinction between observables and unobservables or even the disqualification that the experimental results of scientific research point to the discovery of unobservable entities, as is the case of images collected by microscopes. It is hoped, from these preliminary claims, to provide an overview of these disputes from the 1985 book in order, on the one hand, to understand some of the changes in the realist field from van Fraassen's book, and, analogously, to show how realist criticism, in a way, shaped van Fraassen's developments in order to strengthen his position in defense of an empiricist conception in science.